COVID 19: Impact on Nepali Media - Airi, Lal Bahadur (Baneshwor Campus Journal of Academia, 2023)
Outbreaks appear to be exacerbated during the Coronavirus pandemic. This study studies the impact of the Corona pandemic in Nepalese media sector. Conducted using qualitative and quantitative methods, the study shows the short-term and longterm effects of the corona virus on media journalists and audiences. The media house collapsed, journalists were professionally insecure, and Corona had an impact on the overall media access and influence.